2017
DOI: 10.1055/s-0043-116857
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Sexuality, Anatomical Results and Side-effects of Implantation of an Alloplastic Mesh for Cystocele Correction at Follow-up after 36 Months

Abstract: ABSTR AC TIntroduction Pelvic organ prolapse can significantly reduce quality of life of affected women, with many cases requiring corrective surgery. The rate of recurrence is relatively high after conventional prolapse surgery. In recent years, alloplastic meshes have increasingly been implanted to stabilize the pelvic floor, which has led to considerable improvement of anatomical results. But the potential for mesh-induced risks has led to a controversial discussion on the use of surgical meshes in urogynec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 34 publications
9
23
0
12
Order By: Relevance
“…A low complication rate as well as quality of life at a comparable level between patients undergoing the procedure and healthy women were found. Similar conclusions were reached by Fünfgeld C et al [35], who assessed the efficacy of the procedure 12 and 36 months after performing the alloplastic mesh implantation. In their work, the authors focused more on functional assessment and anatomical repair of the defect.…”
Section: Discussionsupporting
confidence: 81%
“…A low complication rate as well as quality of life at a comparable level between patients undergoing the procedure and healthy women were found. Similar conclusions were reached by Fünfgeld C et al [35], who assessed the efficacy of the procedure 12 and 36 months after performing the alloplastic mesh implantation. In their work, the authors focused more on functional assessment and anatomical repair of the defect.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the average scores for prolapse effects on physical and role activities and personal relationships was quiet high at baseline. A previous study carried out in European women also showed similar scores for the same domains [24,38,39]. Daily life for Ethiopian rural women (e.g.…”
Section: Discussionsupporting
confidence: 63%
“…The better QoL scores compared to baseline scores were also observed in all the 3 P-QoL components (PC, PSC and PRC) after 6 months. Previous studies in Western countries using P-QoL instrument also con rmed that correction of POP via alloplastic vaginal meshes can signi cantly improve patients' QoL [24,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Titanium-coated meshes are new products in POP repair, which improved the pelvic floor-related quality of life and sexual function in a prospective multicenter trial [8]. Fünfgeld et al [9] reported a large prospective multicenter study in Germany, with 289 patients who underwent surgery with a titanium-coated polypropylene mesh-kit (TiLOOP® Total 6; pfm medical ag, Germany) and were followed up for a median of 36 months. The recurrence rate for the anterior compartment was 4.5%, and the quality of life improved significantly.…”
Section: Introductionmentioning
confidence: 99%